Agriculture practices to improve soil carbon storage in upland soil - Kätterer, Thomas (Burleigh Dodds Series in Agricultural Science, 2023)
Increasing carbon storage in soils is one way of mitigating climate change. Carbon sequestration in agricultural soils through improved management is particularly interesting, because of low costs and technical readiness. In this chapter, we synthesize current knowledge on the impact of management practices that promote carbon accumulation in upland mineral soils. Following a brief overview of the principles, we summarize results from meta-analyses quantifying these effects in long-term field experiments and discuss problems with upscaling field-derived data to regional or global scale. In a case study, we highlight the gain in soil fertility from increased carbon stocks. Despite uncertainties, there is strong evidence that management practices such as crop rotations, manures, residue retention, and cover crops can promote carbon storage. The most effective practices are those that increase net primary production through fertilization and those that reduce the time without plant cover by introducing cover crops and using perennial crops in rotations.